Agile - The Level of Implementation in Enterprises - Mariusz SOLTYSIK; Karol WLODYKA; Szymon JAROSZ; Malgorzata ZAKRZEWSKA (Communications of International Proceedings, 2021)
The article covers a very wide range of the topic of implementing an agile approach to an organization. It presents the results of a literature review on the causes of Agile implementation, its benefits and the determinant of transition. The article presents the results of empirical research conducted in Poland on the level of implementation of the agile approach to management.
Keywords: Agile implementation; Enterprises; Agile implementation stage